More of the shareable same - Darsana Vijay (Sur le Journalisme, 2023)
EN. This paper shows the disproportionate influence Facebook exercises over Indian journalism and how it induces conformity and isomorphism in the journalistic field by nudging journalists to incessantly produce more of the same “shareable” content. It focuses on the efforts of 7 alternative news startups in South India to diversify news coverage, as gleaned through 11 in-depth interviews. These startups have a clear reformative agenda, criticizing and hoping to distinguish themselves from the mainstream media’s elite-controlled, partisan, sensationalist reporting that ignores issues affecting the marginalized. Key to these startups’ claims to be alternative is the dedicated, ground reporting of issues faced by the LGBTQ+ community, Dalits and Adivasis. As digital-only publications, they depend on Facebook to circulate their content, interact with the audience and earn revenue. Using the theoretical framework of platformization (Nieborg & Poell, 2018), this paper demonstrates how this dependence keeps startups locked in a perpetual loop of precarity, trying to placate the algorithm with shareable content to stay visible, hoping to eventually get enough subscribers to make it on their own. The constant churning of shareable content detracts organizational resources and leaves their content undistinguishable from the mainstream, postponing the realization of independence to a later date.